Learners' perceptions on the importance of learning object metadata for relevance judgement. (1st January 2012) - Balatsoukas, Panos; Garoufallou, Emmanouel; Morris, Anne; O'Brien, Ann; Asderi, Stella; Siatri, Rania
The purpose of this study was to investigate university students' perceptions on the importance of learning object metadata elements for judging the relevance of learning objects. In order to address this objective an online questionnaire survey was conducted using a clustered sampling technique. A total of 252 students responded to the questionnaire. Participants represented different disciplines (for example, from Humanities & Social Sciences to Sciences & Engineering), levels of familiarisation with the web (advanced and novice users) and educational level (postgraduates and undergraduates). The results showed that participants preferred content related and educational metadata elements as well as metadata elements about the date and the language of a learning object as opposed to technical metadata elements or metadata elements about the version of the learning object when judging the relevance of learning objects.